A review of tripped rollover test methodologies. (9th November 2009) - Chou, Clifford C.; Wagner, Christina; Yang, King H.; King, Albert I.
This paper presents a literature review of test methodologies that have been used in automotive safety test laboratories to provide data for development of rollover occupant protection systems, including rollover sensor algorithms, test methodologies and restraint system performance measures. Test methods reviewed in this paper include SAE J2114, side curb trip, corkscrew ramp, critical sliding velocity, deceleration rollover sled, ditch/embankment, soil trip and some misuse tests that have appeared in the literature. Historical development, procedure, application and experience with each method are discussed. Remarks related to test methodologies are made, and issues pertaining to repeatability and dummy performance are discussed. In addition, various component test methodologies are also reviewed. A suite of laboratory tests to represent real world accident events, which is potentially applicable to military vehicles as well as passenger cars, is presented. Additional development trends in test methods that may enhance restraint system deployment algorithms are also highlighted.